Sharing economy, competition and regulation: the case of Uber in the case-law of the Court of Justice of the European Union - Martins, Patrícia Fragoso (2019)
This article deals with the judgments of the Court of Justice of the European Union on the Uber cases, highlighting some implications of those judgments in the fields of competition and regulation. Uber is widely referred to as the paramount example of sharing economy. With this background, there has been intense debate on the need for a new regulatory framework and on the avenues left open by competition law. Although not addressing said issues directly, by considering Uber a carriage company, and not merely an electronic platform, the Court of Justice has contributed to “thicken the plot” on both these fronts.